HYGIENIC ASSESSMENT OF WORKING CONDITIONS AND OCCUPATIONAL RISK IN COAL INDUSTRY WORKERS - Вера Викторовна Кислицына; Дмитрий Вячеславович Суржков; Дина Викторовна Пестерева; Ирэна Юрьевна Мотуз; Варвара Адамовна Штайгер (Медицина в Кузбассе)
The aim of the research was to assess the risk of developing occupational diseases in coal pit workers based on the hygienic characteristics of working conditions in order to develop preventive measures.